Indigenous Small-Numbered Peoples of North of Yakutia in Focus of Academic Research in Late 1980s — Early 1990s - A. A. Suleymanov (Научный диалог, 2021)
A historical analysis of research conducted during 1988—1991 by employees of the USSR Academy of Sciences to identify the socio-economic and ethnocultural situation of the indigenous small-numbered peoples of the North living in Yakutia is presented in the article. At the same time, the main attention is paid to those materials that most representatively reflect the changes that have occurred in the assessment by scientists of the consequences of the state policy carried out in the Soviet period in the national history of the state policy for indigenous ethnic groups. The sources for the preparation of the article were archival materials identified by the author, as well as published documents and scientific literature data. The work carried out made it possible to determine the main directions of the research, which focused mainly on understanding the impact of management decisions taken by the authorities, as well as changes in the state of the environment under the influence of intensive industrial development on the traditional culture and economy of indigenous peoples. The presented material testifies to the fact that at the turn of the 1980s and 1990s, Yakutia actually found itself at the forefront of criticism of the state policy pursued towards the indigenous peoples of the North through-out most of the Soviet period.